Micro-Computed Tomography: Teknologi pencitraan mikroskopis berbasis Computed Tomography dan pengunaannya dalam analisis kualitas tulang - Fadhlil Ulum Abdul Rahman; Azhari Azhari; Lusi Epsilawati; Ria Noerianingsih Firman; Farina Pramanik (Ikatan Radiologi Kedokteran Gigi Indonesia, 2020)
Objectives: The literature review will briefly review the development of micro-CT as a microscopic radiographic modality in the field of dental research for bone analysis Literature Review: Bone quality values ​​represent the mechanical and biological characteristics of bone mass; structural properties including geometry, macrostructure, and microstructure; and tissue properties including modulus elasticity, mineral density, collagen quality, and character cells and bone marrow. Assessment of bone quality is carried out clinically, both locally and systemically, for various disease or therapeutic conditions. The use of micro-CT is growing prominently and effectively as a modality for analysis and evaluation of bone quality because various morphometric parameters to the microstructural level can be obtained. It applies to the analysis of osseointegration of dental implants and the healing conditions of pathological defects. Conclusion: In conclusion, micro-CT with very high resolution is accurate in the analysis of bone quality because the imaging results can provide microstructure morphometric values ​​in osseointegration conditions after dental implant installation and post-fracture biomechanical characteristics, which can be an essential scientific basis for various experimental bone analysis research designs.